The Effect of the Interaction between the Discovery Type across Mobile Applications and the Cognitive Styles in Development of Environmental Awareness among Students of Primary School - Al-Ghamdi, Sharifah Saad Aqeel; Filimban, Ghadeer Zainuddin (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify The Effect of the Interaction between the Discovery Type across Mobile Applications, and the Cognitive Styles in Development of Environmental Awareness among female Students of Primary School in Jeddah, through the experimental treatment of the content of the unit "My environment" in the fifth grade curriculum the second semester in the course of family education.The semi-experimental approach was used, the researcher designed the mobile application And preparing environmental awareness scale. The sample consisted of (106) female primary school students, divided into four groups according to cognitive style (Impulsive/ Reflective), and the Discovery Type used (free/guided). After analyzing data by appropriate statistical methods, The study found multiple results: There is also a statistically significant difference at (α ≥ 0.05) between the mean scores of the primary stage students in the post-application of the environmental awareness scale due to the fundamental effect of the Interaction between the pattern of discovery through mobile (free/ guided) and cognitive style (Impulsivity/Reflectivity). The researcher recommended to train female teachers to employ a discovery type in mobile learning applications, , and in the teaching of various courses.
Keywords: Discovery Type; Mobile Applications; Cognitive Style; Environmental Awareness